2020
DOI: 10.1007/s11104-020-04703-0
|View full text |Cite
|
Sign up to set email alerts
|

Crops and their wild progenitors recruit beneficial and detrimental soil biota in opposing ways

Abstract:  It is widely known that conventional agricultural practices, like tillage or monocropping, promote negative plant soil feedbacks (PSFs). However, the effect of crop domestication on PSF remain less clear. Evolution under cultivation changes crop genotypes, which might alter their interactions with soil organisms, including mutualists and antagonists, and lead to shifts in soil legacies and feedbacks.  We conducted a two seasons PSF experiment using ten crop species and their wild progenitors. In season one,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 94 publications
2
9
0
Order By: Relevance
“…Yet, some studies struggle to find differences between AMF communities even among distinct plant hosts [ 33 ], and limited information is available on the link between plant genetic makeup and AMF communities. There is, however, evidence that plant breeding, which significantly changes the crop genetic makeup, affects also the host-AMF interaction [ 35 ]. In wheat, for example, it has been demonstrated that cultivars differ in terms of AMF root colonization intensity, nutrient uptake, growth response and root-inhabiting AMF community composition [ 36 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Yet, some studies struggle to find differences between AMF communities even among distinct plant hosts [ 33 ], and limited information is available on the link between plant genetic makeup and AMF communities. There is, however, evidence that plant breeding, which significantly changes the crop genetic makeup, affects also the host-AMF interaction [ 35 ]. In wheat, for example, it has been demonstrated that cultivars differ in terms of AMF root colonization intensity, nutrient uptake, growth response and root-inhabiting AMF community composition [ 36 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Plant defense against pathogens typically comes with the cost of reduced growth, but plants can ameliorate the cost of resistance by maintaining a protective microbiome in the rhizosphere (Karasov et al, 2017 ). Domestication and breeding of crops changed the microbial communities in their rhizospheres (Pérez-Jaramillo et al, 2016 ; Pieterse et al, 2016 ; Martín-Robles et al, 2020 ). Wild barley genotypes allocated more resources than elite cultivars to root growth compared with stem growth (Alegria Terrazas et al, 2020 ), which may alter root exudates and consequently the assembly of microbial communities in the rhizosphere.…”
Section: Discussionmentioning
confidence: 99%
“…Microbiomes in the rhizosphere of plants are in part intimately associated with particular plant species and play a key role in plant growth and health (Mendes et al, 2011;Liu et al, 2020). Roots are surrounded by a rich diversity of microorganisms that support them in nutrient acquisition, production of growth factors, defense against pathogens, and mitigate their exposure to adverse environmental stress depending on species composition (Lugtenberg, 2015). The plant alongside its associated microbiota is considered as a unit of selection termed "holobiont" that determines the plant performance and productivity (Gopal and Gupta, 2016;Rosenberg and Zilber-Rosenberg, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…According to Pérez-Jaramillo et al [13], there is an impact of the domestication of crops on soil management, phenotypes, physiology, and the diversity of rhizobacteria associated with crops; the domestication process may have had an adverse impact on the composition and functions of the associated microbiota. In this regard, Martín-Robles [14] states that colonization by mycorrhizae is lower and the infection rate by nematodes is higher in the roots of plants that grow in soils previously cultivated by domesticated plants. Furthermore, domesticated plants showed lower mycorrhizal colonization and higher nematode infection rates than their wild progenitors.…”
Section: Crop Domestication and Microbial Diversitymentioning
confidence: 99%